McDonald's: Internationalisation VS Globalization - The Marketing Mix - Hussain, Shuhaila (2004)
The case will focuses on the marketing mix of McDonald's. Using the strategical and tactical models, the case will analyze how McDonald's formulate their marketing mix strategy in order to adapt with internationalization elements according to fast food markets.